An interpretive approach to model educational games: Learning theories domain using multi-domain framework - Ahmad, M. (Institute of Electrical and Electronics Engineers Inc., 2015)
Game-based learning or educational games are known to be a highly engaging learning system which is incorporated with features that could be addictive for learners to provide effective learning. To model and develop an effective educational game has constantly been a challenge for game developers as they need to understand the depth and relationships between theoretical foundations, game environment, rules and regulations, and the learner's achievement to precisely recognize the goal embedded in the educational game. Thus, the authors have proposed a multi-domain framework with extracted relationships through systematic literature review. These relationships are verified through qualitative interviews with eight (8) game-based learning experts to validate the relationships. This paper presents six (6) implicit relationships based on learning theories domain and discusses their relevancy with game environment, game play (rule and regulations), and subject-matter (learners, teachers) by applying interpretive hermeneutic approach of qualitative study. Consequently, this paper concludes six (6) explicit relationships for game developers to reflect on during the development process of educational games. Â© 2015 IEEE.